The conditional contribution mechanism for repeated public goods: the general case [research data] - Oechssler, Joerg; Reischmann, Andreas; Sofianos, Andis (Universität, 2022)
We present a new and simple mechanism for repeated public good environments. In the Conditional Contribution Mechanism (CCM), agents send two messa...
Gesehen am 08.06.2022
Keywords: Forschungsdaten; Datenbank